2015
DOI: 10.4236/ajac.2015.61004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen in Adsorption and Direct Dissociation of CO on Fe (100) Surface: A DFT Study

Abstract: Density functional theory was employed to investigate the effect of the hydrogen in the adsorption and direct dissociation of CO on Fe (100) surface. The preadsorption of hydrogen with coverages of 0, 1/3 and 2/3 monolayer (ML) was used in the present investigation. In the case of 1/3 ML of hydrogen, two configurations of adsorption were studied. The presence of hydrogen shows a major transference of electronic density from Fe surface to CO adsorbed, increasing the adsorption energy of CO from 2.00 eV in clean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…The first three layers were fixed at the bulk position and the other two were allowed to relax describing the (100) surface where H is adsorbed. Hydrogen-adsorption energy is converged for a p(2x2) model in good agreement with calculations of H adsorption on F e(100) performed by Amaya et al [19,20,21] and by Sorescu [29].…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…The first three layers were fixed at the bulk position and the other two were allowed to relax describing the (100) surface where H is adsorbed. Hydrogen-adsorption energy is converged for a p(2x2) model in good agreement with calculations of H adsorption on F e(100) performed by Amaya et al [19,20,21] and by Sorescu [29].…”
Section: Methodssupporting
confidence: 81%
“…Ferrin et al [3] have investigated diffusion of hydrogen from the surface to the bulk using the P W 91 density functional [15], whereas Kristinsdóttir et al [4], have studied surface diffusion on several metals by means of RPBE [16]. In addition, the calculations performed with GGA-PBE functionals, have been widely accepted in the scientific community and have been extensively used in systems with periodic boundary conditions [17,18,19,20,21]. Even with the mentioned references, the fcc (100) surfaces of Au, Cu, Ag and P t,…”
Section: Introductionmentioning
confidence: 99%
“…This topic has been revisited by a number of recent works. [23][24][25][26][27] While a dense CO-coverage (≤0.25 monolayer) is commonly considered, we have shown that the dissociation barrier is greatly reduced at a dilute coverage (up to 0.0625 monolayer), 28 due to the unrestricted relaxation of the Fe lattice. However, the presence of intrinsic defects is a likely candidate that can significantly affect the carburisation process and has not been considered yet.…”
Section: Introductionmentioning
confidence: 75%
“…In practice, more complex reaction pathways would be possible as a number of other molecules and sites that could act as activator, such as H and other reactive hydrocarbons and surface defects, are generally present and could assist the dissociation process [13,14]. Recent works on the 100 surface show that high-coverage presence of H increases the rate of carburization by reducing the dissociation barrier [13,15]. On the other hand Cu impurities on the surface increase the dissociation barrier and prevent C atoms to be adsorbed into the surface [14].…”
Section: Introductionmentioning
confidence: 99%
“…After almost a decade, this topic has been revisited by many researchers in recent years [10,11,[13][14][15]26]. There are several reasons for this renewed interest, of which, notable from the perspective of computational science, is the advancement in computational power that is necessary for surface calculations with the computationally demanding nudged elastic band method.…”
Section: Introductionmentioning
confidence: 99%